La guerra nell’epoca delle macchine intelligenti (e la paura) - Cuomo, Vincenzo (Mechane, 2023)
The main objective of the essay is to reflect on the aporia of war, which manifests itself in the disagreement between its technical rationality and its irrational and ‘drive’ character. The realisation of intelligent machines today seems to realise a goal that has been nagging military commanders for centuries: to reduce or eliminate the contribution of the human element from the battlefield. However, behind the widespread concern that ’intelligent’ machines will behave like ‘predatory machines’, there is always the fear that they will behave like human beings, autonomously conducting war. Indeed, the problem continues to be that of war, before that of (intelligent) weapons of war. However, the paradox on which, in conclusion, this essay reflects – through a deconstructive commentary on some of Heidegger’s theses – is that what could act as a brake on the irrationality of war is still something to do with that irrationality: fear.